Kualitas Mikrobiologi Dendeng Sapi yang di Curring dengan Ekstrak Rosella (Hibiscus sabdariffa. L) - Maria I. Nesi; Stefanus Sio; Kristoforus W. Kia (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2019)
The purpose of this study was to determine the antibacterial activity of rosella extract (Hibiscus sabdariffa L.) on the growth of Staphylococcus aureus bacteria and the microbiological quality of beef jerky which was curing wet with rosella extract. This study uses concentrations of rosella extract 40% and 60%. Positive control using nitrate or belching 0.2 g and negative control using aquades. This type of research is an experimental laboratory. Test the antibacterial activity of rosella extract against S. aureus using the diffusion method by means of wells. As for the microbiological quality of beef jerky using dilution method. The results showed that the concentration of rosella extracts of 40% and 60% had the ability to inhibit the growth of S. aureus bacteria with an average of 3.41 mm and 4.03 mm. Whereas positive and negative controls do not have the ability to inhibit bacterial growth. The results of the microbiological quality test of beef jerky showed that rosella extract had bacteriostatic ability with mean values obtained 28.33 and 8.67. The conclusion of this study using ANOVA statistical analysis and Duncan's advanced test with a significant level of 0.05 shows that rosella extract has a significant level in inhibiting S.aureus bacteria and is able to suppress microbial growth in beef jerky.